Alfred Hitchcock : filming our fears - Adair, Gene (Oxford portraits., 2002)
Alfred Hitchcock is a fascinating look at the life of one of the most influential filmmakers in the world -- a man known for his portly profile and distinct, leery voice almost as much as for his groundbreaking movies. From Hitchcock's first film, Blackmail -- the first British movie with sound -- to his blockbuster Hollywood successes, Psycho, The Birds, Rear Window, and Vertigo.